2022
DOI: 10.3390/jof8111153
|View full text |Cite
|
Sign up to set email alerts
|

The Role of the Cutaneous Mycobiome in Atopic Dermatitis

Abstract: Atopic dermatitis is a chronic inflammatory skin disorder characterized by eczematous lesions, itch, and a significant deterioration in the quality of life. Recently, microbiome dysbiosis has been implicated in the pathogenesis of atopic dermatitis. Changes in the fungal microbiome (also termed mycobiome) appear to be an important factor influencing the clinical picture of this entity. This review summarizes the available insights into the role of the cutaneous mycobiome in atopic dermatitis and the new resear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 144 publications
0
9
0
Order By: Relevance
“…Although children with AD had a more diverse microbiome in non-lesional skin compared to adults, dysbiosis occurred within skin lesions due to an impaired barrier ( 20 ). Dysbiosis was associated with reductions in Streptococcus , Cutibacterium and Malassezia , accompanied by increases in Staphylococcus aureus , suggesting an antagonistic relationship between skin commensals ( 20 , 21 ). Streptococcus may inhibit S. aureus growth by producing hydrogen peroxide ( 27 ), whereas Cutibacterium and Corynebacterium are involved in porphyrin metabolism which may further suppress S. aureus colonization ( 20 , 28 ).…”
Section: Atopic Dermatitismentioning
confidence: 99%
See 1 more Smart Citation
“…Although children with AD had a more diverse microbiome in non-lesional skin compared to adults, dysbiosis occurred within skin lesions due to an impaired barrier ( 20 ). Dysbiosis was associated with reductions in Streptococcus , Cutibacterium and Malassezia , accompanied by increases in Staphylococcus aureus , suggesting an antagonistic relationship between skin commensals ( 20 , 21 ). Streptococcus may inhibit S. aureus growth by producing hydrogen peroxide ( 27 ), whereas Cutibacterium and Corynebacterium are involved in porphyrin metabolism which may further suppress S. aureus colonization ( 20 , 28 ).…”
Section: Atopic Dermatitismentioning
confidence: 99%
“…, whereas Cutibacterium, Corynebacterium, Staphylococcus, Lactobacillus, Finegoldia and Anaerococcus are more abundant in adults. Over 100 fungal species have been identified on healthy skin, with most belonging to the phyla Ascomycota ( 21 ). Increased sebum production and structural changes after puberty may facilitate colonization with lipophilic microbes including Cutibacterium, Corynebacterium and Malassezia , replacing Streptococcus and Candida ( 20 , 22 ).…”
Section: Atopic Dermatitismentioning
confidence: 99%
“…Changes in the mycobiome have also been implicated in the pathogenesis and clinical presentations of skin diseases, such as atopic dermatitis [ 58 ]. The primary fungal imbalances observed in head and neck variants of atopic dermatitis have been in the rates of Malassezia and Candida , and appear to be associated with fungal antigens producing robust immune responses, sensitization, and skin lesions [ 58 ]. Antifungal immune system responses include C-type lectin receptors, IL-1β, and inflammasomes [ 59 ].…”
Section: Mycobiome Dysbiosismentioning
confidence: 99%
“…In atopic dermatitis skin lesions, it has been found that Malassezia levels are decreased, and filamentous fungi are increased, along with a positive correlation between Candida and Staphylococcus [ 60 ]. Understanding and elucidating mycobiome implications of this nature could help in the development of more effective treatments for the ailments [ 58 ].…”
Section: Mycobiome Dysbiosismentioning
confidence: 99%
“…The major medical co-morbidities associated with AD are microbial infections, specifically SA [14][15][16][17][18], affecting > 90% of patients. SA colonization is related to skin barrier disruption, a predominant Th2 immune response, elevated IgE levels specific to staphylococcal enterotoxin, and a reduction in skin microbial diversity.…”
Section: Introductionmentioning
confidence: 99%